PENGARUH PERBEDAAN UMUR DAN CARA PENGERINGAN TERHADAP RENDEMEN DAN KUALITAS MINYAK NILAM = EFFECT OF AGE AND DRYING TECHNIQUES ON THE YIELD AND QUALITY QF NILAM OIL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Oil recovery from nilam leaves in Indonesia is still low. It is due to lack of information about age and drying technique which will give the optimum yield. This research will try to solve the problem. Nilam leaves at age of 3, 4 and 5 months were harvested from nilam plantation at Baturaden, Central Java. Trhee drying techniques were used, i.e. air drying, sun heat drying and solar drying. Each batch of 7 leg of leaves was distilled using steam at three replications. Oil quality tested were specific gravity, polariza-tion angle, ray deflection angle, alcohol 95% solubility and fat content. The results showed that age 4 and 5 months and drying technique using sun heat and solar drying, give better yield and quality of nilam oil.